(untitled) (The Journal of Psychology and Sociology, 2012)
In article the family which unlike any form of marriage, includes all system of the public relations – marriage and related, legal and social, economic and household and ecological, moral and ethical, psychological and emotional is considered. Therefore the family as a social community is the primary element, mediating communication of the personality with society. According to the author of article, the civil marriage isn’t an alternative to family.